HUBUNGAN DUKUNGAN KELUARGA DENGAN RESILIENSI LANSIA SELAMA MASA PANDEMI COVID-19 - Putra, Gede Rionald Ariwahyu; Utami, Putu Ayu Sani; Pramitaresthi, I Gusti Ayu (Coping: Community of Publishing in Nursing; Vol 11 No 5 (2023): Oktober 2023DO - 10.24843/coping.2023.v11.i05.p02, 2023)
Covid-19 pandemic is a vulnerable situation that may create a lot of problems and lead to the lower resilience level among elders. Vulnerability of elders to various problems such as anxiety and illness during pandemic causes elders need support from others. Family is the closest environment for elders during pandemic. Family is one of the important support sources for elder. This study aimed to determine the relationship between family support and elder resilience during Covid-19 pandemic. This study was a correlative descriptive study and used cross-sectional approach. Respondents of 33 people were obtained through purposive sampling technique. Data collection using family support questionnaire and Connor Davidson Resilience Scale 10 items. The data analysis used the Spearman Rank test. The study result showed correlation coefficient value = 0,776 and p-value = 0,000 (? = 0,05) which mean there were a strong positive correlation between family support and elder resilience during Covid-19 pandemic. Adequate interactions and providing daily needs for the elderly need to be carried out by the family, so that they always feel cared for and their resilience is maintained during the Covid-19 pandemic.